Analisis Pengembangan Objek Wisata Religi Burake Kecamatan Makale Kabupaten Tana Toraja - Pasang, Frischalin Pniel; Lobja, Xaverius Erick; Ramadhan, Muhamad Isa; Nugroho, Cahyadi; Otoluwa, Yemima (Jurusan Pendidikan Geografi Universitas Negeri Manado, 2024)
Burake Religious Tourism Attraction is one of the tourist attractions built in a limestone hilly area (karst) on which the tallest statue of Jesus Christ in the world is built. This research aims to find out how efforts are made to develop the Burake Religious Tourism Object. The research method used is descriptive quantitative with SWOT analysis techniques. Data collection techniques in this research are observation, interviews, documentation and literature study. The research results show that based on the ALI weighting results, the internal factor of strength has a score of 3.60, which means the internal position is strong and the ALE on external factors of opportunity has a score of 3.70, which also means the external position is strong. Several things that need to be pursued in developing the Buntu Burake Religious Tourism Object are tourist attraction, accessibility, promotion, potential, facilities and infrastructure.